A comparison of attributions, self-esteem, anxiety, and parental attachment in sexually abused and non-abused Korean children. Issue 2 (2nd July 2016) - Choi, Kyung-shick; Englander, Elizabeth; Woo, Youngki; Choi, Jisun; Kim, Ji-eun; Kim, Hyejung
ABSTRACT: This study attempts to address the dearth of information about child sexual abuse (CSA) and psychological functioning in Korean children by measuring the psychological impact of sexual abuse on children in South Korea. The original data were collected on 92 sexually abused children (age 13 or younger) who underwent medical forensic interviews and psychological evaluations prior to treatment. This study collected additional data reflecting specific psychological evaluations from a control group drawn from five randomly chosen elementary schools. The psychological impact on the group of sexually abused children was compared to the control group via the assessment of four major psychological diagnostic criteria: (1) Child Attribution Perception Scale (CAPS), (2) Self-Esteem Scale (SES), (3) Parental Behavior Scale-Child reporting (PBS), and (4) State Trait Anxiety Inventory-Children (STAI-C). Using structural equation modeling, the findings indicated that the abused and control-group children differed significantly on these four psychological criteria. Policy recommendations addressing victim, parent, and health provider needs are reviewed.